INFLUENCE OF EXTENSIVE READING STRATEGY ON STUDENTS’ INTEREST IN READING COMPREHENSION - Atinuke, Owodunni Mary (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
This study was designed to investigate the influence of extensive reading strategy on learners’ interest in reading comprehension. Design of the research was pretest-posttest non-equivalent control group design of quasi-experimental research design. All the Junior Secondary school (JSS) two English Studies students in Kwali Area Council of Federal Capital Territory (FCT), Abuja participated in the study. The study sample was 210. Two research questions and three null hypotheses tested at .05 level of significance. The instrument used to gather data for analyses was Reading Comprehension Interest Inventory Test (RCII). Data collected were analyzed using inferential statistics. The result shows that extensive reading strategy is more effective in arousing learners’ interest in reading comprehension and female students show more interest in reading comprehension than boys. There was no interaction influence of extensive reading strategy and gender on interest of (JSSII) students in reading comprehension. The study recommended among others that English language educators should use extensive reading strategy to stimulate learners’ interest and more time allocated in the school for extensive reading. This will stimulate their students’ interest and also improve their performance in reading comprehension.